2018
DOI: 10.1111/cmi.12864
|View full text |Cite
|
Sign up to set email alerts
|

TheAspergillus fumigatustranscription factor AceA is involved not only in Cu but also in Zn detoxification through regulating transporters CrpA and ZrcA

Abstract: Copper (Cu) and zinc (Zn) are essential nutrients for both pathogens and hosts; however, their excess accumulation is toxic for all cells. The Aspergillus transcription factor AceA has been identified having function for Cu detoxification through up-regulation of the expression of the P-type ATPase, CrpA. Here, we demonstrate that Aspergillus fumigatus CrpA is involved in both Cu and Zn detoxification and a putative metallothionein AfCrdA plays a major function in Cu detoxification, and a putative transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 52 publications
1
70
0
Order By: Relevance
“…In the case of Cd, with 250 μM Cd(NO 3 ) 2 , a very faint band was visible at 120′ after exposure. It has recently been reported that AfCrpA also contributes to Zn resistance in A. fumigatus (Cai et al 2018). These results indicate that even if it might have some role in other heavy metal detoxification, copper is the principal ion transported by CrpA (Antsotegi-Uskola et al 2017).…”
Section: Copper Detoxificationmentioning
confidence: 92%
See 2 more Smart Citations
“…In the case of Cd, with 250 μM Cd(NO 3 ) 2 , a very faint band was visible at 120′ after exposure. It has recently been reported that AfCrpA also contributes to Zn resistance in A. fumigatus (Cai et al 2018). These results indicate that even if it might have some role in other heavy metal detoxification, copper is the principal ion transported by CrpA (Antsotegi-Uskola et al 2017).…”
Section: Copper Detoxificationmentioning
confidence: 92%
“…The copper detoxification process is orchestrated by the transcription factor AceA. In A. fumigatus, AfAceA is also involved in zinc detoxification (Cai et al 2018). The characteristic domains that identify this TF are the BCu fist^DNA binding domain, and the numerous cysteine residues arranged in CxC-CxxC segments through the protein sequence, identified as necessary for function in S. cerevisiae (Hu et al 1990).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the cell is overloaded with copper, the low-affinity copper-responsive transcription factor AceA is activated to promote the expression of CrdA, a metallothionein [ 18 ], to protect the cell from copper toxicity [ 19 ]. The copper concentration in the cell is also known to be controlled by expression of CrpA, a copper exporter [ 19 , 20 ]. CrpA is a P-type ATPase copper transporter located on the surface of the cell that pumps copper out of the cell to prevent excessive copper accumulation inside the cell.…”
Section: Introductionmentioning
confidence: 99%
“…fumigatus (Moreno et al , ). In fungi, excess zinc is stored in the vacuole (Cai et al , ; Eide, ). Unlike iron homeostasis, where the single transcription factor HapX regulates adaptation to both iron‐limiting and iron excess conditions (Gsaller et al , ), ZafA is not involved in zinc detoxification.…”
Section: Introductionmentioning
confidence: 99%